Question) Q = x 1 a - b ) 1 a - c   x x 1 b - c 1 b - a   x x 1 c - a 1 c - b

Dear student
Q=1xa-b1a-c×1xb-c1b-a×1xc-a1c-b=x(b-a)1a-c×x(c-b)1b-a×x(a-c)1c-b=xb-aa-c ×xc-bb-a×xa-cc-b=xb-aa-c+c-bb-a+a-cc-b=xb-a2c-b+c-b2a-c+a-c2b-aa-cb-ac-b=xb2+a2-2abc-b+c2+b2-2bca-c+a2+c2-2acb-aa-cb-ac-b=xb2c-b3+a2c-a2b-2abc+2ab2+c2a-c3+ab2-b2c-2abc+2bc2+a2b-a3+bc2-ac2-2abc+2a2ca-cb-ac-b=x-6abc-a3-b3-c3+3a2c+3ab2+3bc2a-cb-ac-bIdentity used:1an=a-nam×an=am+naman=am-namn=amn
Regards

  • 0

Dear student
Q=1xa-b1a-c×1xb-c1b-a×1xc-a1c-b=x(b-a)1a-c×x(c-b)1b-a×x(a-c)1c-b=xb-aa-c ×xc-bb-a×xa-cc-b=xb-aa-c+c-bb-a+a-cc-b=xb-a2c-b+c-b2a-c+a-c2b-aa-cb-ac-b=xb2+a2-2abc-b+c2+b2-2bca-c+a2+c2-2acb-aa-cb-ac-b=xb2c-b3+a2c-a2b-2abc+2ab2+c2a-c3+ab2-b2c-2abc+2bc2+a2b-a3+bc2-ac2-2abc+2a2ca-cb-ac-b=x-6abc-a3-b3-c3+3a2c+3ab2+3bc2a-cb-ac-bIdentity used:1an=a-nam×an=am+naman=am-namn=amn
Regards

  • 0
What are you looking for?